PERANAN HARGA, PROMOSI DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN MCDONALD’S - Damar; Kristiawan, Allen (FEB Universitas Sam Ratulangi Manado, 2023)
The times and era of globalization continue to develop and experience changes, especially in the food industry. One of them is McDonald's fast food which has been present in Indonesia for a long time and is very popular with the public. Because people look at the criteria of price, promotion and product quality which can give them a sense of customer satisfaction. This research was conducted with the aim of testing and analyzing whether there is an influence of price, promotion and product quality on customer satisfaction. The sample that will be used is the people of Bandung who buy McDonald's products. The sampling technique uses non-probability sampling and the sample type uses purposive sampling. The data collection technique is by distributing questionnaires and the target number is 170 respondents. The data processing technique uses multiple regression analysis with the help of the SPSS application. From the research results it can be concluded that there is a positive and significant influence of price, promotion and product quality on customer satisfaction.